The Christian educator's handbook on Children's ministry reaching and teaching the nest generation - Choun, Robert J.; Lawson, Michael S. (Grand Rapids, MI Baker, 1998)
Includes bibliographical references.
Originally published : The complete handbook for children's ministry, Nashville, TN : T. Nelson, c.1993 ; cf.
Keywords: Church work with children; Christian education of children